Responses of peripheral blood mononuclear cells to moderate exercise and hypoxia. Issue 10 (3rd October 2015) - Morabito, C.; Lanuti, P.; Caprara, G. A.; Guarnieri, S.; Verratti, V.; Ricci, G.; Catizone, A.; Marchisio, M.; Fanò‐Illic, G.; Mariggiò, M. A.
Abstract : The purpose of this study was to analyze the physiological features of peripheral blood mononuclear cells (PBMCs) isolated from healthy female trekkers before and after physical activity carried out under both normoxia (low altitude, < 2000 m a.s.l.) and hypobaric hypoxia (high altitude, > 3700 m a.s.l.). The experimental design was to differentiate effects induced by exercise and those related to external environmental conditions. PBMCs were isolated from seven female subjects before and after each training period. The PBMCs were phenotypically and functionally characterized using fluorimetric and densitometric analyses, to determine cellular activation, and their intracellular Ca 2+ levels and oxidative status. After a period of normoxic physical exercise, the PBMCs showed an increase in fully activated T lymphocytes (CD3 + CD69 + ) and a reduction in intracellular Ca 2+ levels. On the other hand, with physical exercise performed under hypobaric hypoxia, there was a reduction in T lymphocytes and an increase in nonactivated B lymphocytes, accompanied by a reduction in O2 − levels in the mitochondria. These outcomes reveal that in women, low‐ to moderate‐intensity aerobic trekking induces CD69 T cell activation and promotes anti‐stress effects on the high‐altitude‐induced impairment of the immune responses and the oxidative balance.